2013
DOI: 10.1111/trf.12435
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cell yield calculated using preapheresis absolute CD34+ cell count, peripheral blood volume processed, and donor body weight accurately predicts actual yield at multiple centers

Abstract: The formula of Pierelli et al. is associated with a PPV that is high, moderate, and relatively low for the corresponding predicted CD34+ doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 19 publications
5
25
0
Order By: Relevance
“…In our cohort of sibling donors, the short-term side effects of G-CSF 16 μg/kg were predominantly bone pain, headache and fatigue with grade 1-2 according to CTC criteria. No serious side effect was observed, it was in concordance with other studies [7,27]. A transient state of hypercoagulalibity that could give to rise to thrombotic complications especially in older sibling donors could be a potential hazard of PBSC mobilization with G-CSF [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our cohort of sibling donors, the short-term side effects of G-CSF 16 μg/kg were predominantly bone pain, headache and fatigue with grade 1-2 according to CTC criteria. No serious side effect was observed, it was in concordance with other studies [7,27]. A transient state of hypercoagulalibity that could give to rise to thrombotic complications especially in older sibling donors could be a potential hazard of PBSC mobilization with G-CSF [7].…”
Section: Discussionsupporting
confidence: 90%
“…The preapheresis count of CD34 cells in peripheral blood seems to be another important predictor of successful PBSC harvest [2,7,27].Our results confirm a strong correlation between CD34 cell counts before the first apheresis and the overall amount of CD34 cells after mobilization (p< 0.001).…”
Section: Discussionsupporting
confidence: 76%
“…It is important to study prediction algorithms specifically in allogeneic donors, however, given previous reports of differing results in allogeneic compared to autologous donors undergoing same‐device MNC protocols. Only three of the five validations that included allogeneic donors published parameters specific to the allogeneic donors. One study found a slightly lower correlation between the predicted and actual amount collected (compared to autologous donors), and two found a higher and lower CD34+ CE (compared to autologous donors), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many centers, even some that use prediction algorithms, may still process a fixed number of liters, total blood volumes, or volume per donor body weight . This may be because, rather than predicting volume to process as the dependent outcome variable, six of the eight validated algorithms (Table ) predict CD34+ cells collected to reach the target CD34+ dose. Some of the algorithms may be difficult to adopt because of the need for linear regression or the lack of consideration of recipient weight for use in allogeneic recipients .…”
Section: Validated Prediction Algorithms For Desired Product Cd34+ Tamentioning
confidence: 99%
See 1 more Smart Citation